DAMPAK PENERAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PT. AMMAN MINERAL NUSA TENGGARA (PT. AMNT) DI KABUPATEN SUMBAWA BARAT - K Kurniawansyah; Ishak Rahman; S Susanah; Subhan Purwadinata (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This research was conducted with the aim of knowing the impact of implementing corporate social responsibility (CSR) at PT. Amman Mineral Nusa Tenggara (PT. AMNT) in West Sumbawa District on the development of a laying chicken business in Benete Village. This type of research is a comparative study which aims to compare the income of laying chickens in Benete Village, West Sumbawa District before and after the implementation of CSR PT. Amman Mineral Nusa Tenggara (PT. AMNT). The data used is qualitative data in the form of informants' answers to questions given related to the object of research and collected through direct interviews with informants. The informants who were the source of the data in this study were the chief of the laying chicken farmer group in Benete Village and the human capital supervisor of PT. AMNT. Data analysis was performed using a paired sample test technique. Based on the results of the two-difference test analysis, the average value of t-count is 2.246, which is greater than the t-tabel value at the degree of confidence (df) = 11 and at the 5% significance level, which is 2.201 (2.246>2.201). This implies that there are differences in the income of laying chickens in Benete Village before and after the implementation of PT. AMNT in West Sumbawa District. The average income of laying chickens in Benete Village before the implementation of PT. AMNT is Rp. 48.640.417-, but there was a significant increase in the average income after the implementation of CSR PT. AMNT becomes Rp. 101.491.250-.